Comparison of the accuracy of implant placement using a simple guide device and freehand surgery - Yu-Jin Kim; Jungeun Kim; Jae-Rim Lee; Hee-Sun Kim; Hye-Young Sim; Ho Lee; Yoon-Sic Han (Elsevier, 2024)
Background/purpose: In clinical settings, there may be a need for a guide device that is simple and enhances the positioning accuracy of prosthetics. This study aimed to compare the accuracy of implant positioning using two methods: implant placement with a simple guide device (SGD) and freehand surgery. Materials and methods: A total of 103 patients were randomly assigned to the control or study group. In the control group, implant placement was performed using the freehand technique. In the study group, implant placement was conducted with an SGD. Implant positioning accuracy was assessed by measuring how much the central position, fixture angulation, and fixture position differed from the ideal implant position based on periapical radiographs and cone-beam computed tomography images. In patients with double implants, parallelism between the two fixtures was also measured. Results: There were 124 subjects, with 84 having single implants (42 in the control group and 42 in the study group) and 40 having double implants (20 in the control group and 20 in the study group). Utilization of the SGD for both single and double implant placement improved the accuracy of the central position, fixture angulation, and fixture position (P < 0.05). Additionally, in double implantation cases, it significantly enhanced parallelism between the two fixtures (P < 0.001). Conclusion: These findings suggest that use of an SGD leads to more accurate implant placement compared with freehand surgery taking into account the final prosthetic restoration.